PENINGKATAN PERKEMBANGAN MOTORIK KASAR DI TAMAN KANAK-KANAK GEMBALA BAIK PONTIANAK - Rita, Helena; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this research is to know the improvement of gross motor development after using traditional game of coconut shell in children aged 5-6 years in Kindergarten Good Shepherd Pontianak. in general can be drawn a conclusion that: 1) Learning planning using traditional games of coconut shell to improve gross motor in children aged 5-6 years is categorized as